Pediatric Air Gunshot Penetrating Head Injury with Good Outcome: A Case Report - Yusriandi Ramadhan; Zainal Abidin; Ardik Lahdimawan Lahdimawan (Berkala Kedokteran, 2020)
Abstract: Ball bearing (BB) and pellet guns are non-power guns but their related injuries have been reported worldwide. They represent a significant cause of injury especially among children and teenagers. Their potentially harmful and lethal effects have been well documented in the medical literature since the early 1980s. Fatality rate is closely related to the damaged part of the brain and the level of the damage. In this Case Report we documented a 6-years-old girl was getting shot at the head by herself, who initially want to play around, using her neighbour’s Air gun rifle. The pellet trajectory passed through the left frontal lobe, left temporal lobe, left posterior putamen, posteriorly left crus posterior of internal capsule, left occipital horn of lateral ventricle, left occipital lobe, and ended at left cerebral falx between both medial surfaces of occipital lobes. Directional slope of the pellet was medially upward, with its tracking left Intracerebral Hemorrhage (ICH) with perifocal edema and Intraventricular Hemorrhage (IVH) dominant in the left lateral ventricle. After 8 days management, the patient was discharged from our hospital with stable condition, GCS 15 without any significant neurological deficits. Intracranial intracerebral pellet due to air gun shot injury, may have fatal and lethal manifestation if the pellet damage the eloquent area and/or deep area of the brain (hypothalamus, thalamus and brain stem). If accessible the foreign body or pellet should be removed immediately for better outcome. Keywords: Head Injury, Air Gun Shot, Intracerebral Haemorrhage